Meningkatkan Kemampuan Menulis Cerita Siswa MTs Melalui Model Pendekatan Eksperiental - Rukmini Rukmini; Farida Nugrahani; Suwarto Suwarto (Nusantara: Jurnal Pendidikan Indonesia, 2023)
The writing proficiency of Islamic Junior High School (MTs) students falls short of expectations due to limited literacy, time constraints, and a lack of writing material ideas and references. This study evaluates the effectiveness of the Experiential approach model in enhancing narrative writing skills among ninth-grade students at MTsN 8 Gunungkidul during the 2022/2023 academic year. Using a one-group pretest-posttest design, 63 students were randomly selected from a population of 158 students, divided into an experimental group (IXC) and a control group (IXE). Data were collected through documentation, tests, and observations and analyzed with various methods. The research results indicate that the use of the Experiential approach model significantly improved students' writing abilities in Inspirational Stories compared to the conventional approach. This research serves as a valuable reference for teachers in selecting effective teaching models and for future studies in the field.